Radiopharmacologist’s and Radiochemist’s View on Targeting the Eph/Ephrin Receptor Tyrosine Kinase System - Neuber, Christin (ACS Omega, 2020)
[Image: see text] In the past decade, there have been extensive efforts to open up the Eph/ephrin subfamily of the receptor tyrosine kinase family for diagnostic and therapeutic applications. Besides classical pharmaceutical developments, which focus either on drugs targeting the extracellular ligand binding domains or on the intracellular tyrosine kinase domains of these receptors, there also have been first radiopharmaceutical approaches. Here the focus is on the development of specific and selective probes for molecular imaging, particularly by means of positron emission tomography, and the functional characterization of the Eph/ephrin subfamily in certain target tissues. The aim of this mini-review is to summarize the different approaches toward Eph-targeting radiotracers by using antibodies, peptides, and small molecules and to discuss their radiopharmacological characterization. With regard to the small molecules, further considerations will focus on the design and synthesis of nonradioactive reference compounds and precursors as well as on radiolabeling strategies.